Shari'ah governance for Islamic banking : an analytical study of the Pakistan experience - Jan, Sahibzada Muhammad Wasim (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
The State Bank of Pakistan has introduced a new SharÊÑ'ah governance framework for Islamic banking in Pakistan recently which was influenced by its past and continues to influence the present Islamic banking legal and operational experiences. The research is designed to analyze critically its theoretical, historical, structural and operational aspects. It explores the main theme of SharÊÑ'ah governance framework and its formation in Pakistan's Islamic banking system. It also examines the influence of different regulatory authorities on SharÊÑ'ah governance framework and identifies the roles and responsibilities of each organ in its operational structure. It uses the critical, analytical and comparative methodology. The study is mostly based on the available literature produced in the past and present related to Pakistan's Islamic banking system. The result of the study reveals that SharÊÑ'ah governance is simply a complement of the traditional corporate governance system in addition to its Islamic worldview. The historical study discovers that Islamic banking is a religious and financial need for the large Muslim population of the country. It points out that there is an overlapping situation among the supervisory authorities but no specification is found for a decisive role of any high authority to deal with the Islamic banking issues. The State Bank of Pakistan and its SharÊÑ'ah Board need to be granted with exclusive decisive role regarding Islamic banking matters. It discovers that the present SharÊÑ'ah governance framework is lacking legal and regulatory strength. The composition of the SharÊÑ'ah advisory boards at the central level and the institutional level need more improvements in terms of the number of SharÊÑ'ah advisors and the criteria for their selection and appointment. There is no specific provisions of the roles and responsibilities and privileges of the main organs of the SharÊÑ'ah governance framework which is crucially required by considering the framework implemented by Bank Negara Malaysia. The local regulatory system must be enhanced and the SharÊÑ'ah governance framework should be backed by legal amendments in the current system to prevent any possible systematic disorder.